Expressing Satisfaction in American English and Vietnamese (as Seen from the Categorical Dimension of Directness-Indirectness) - Linh, Nguyễn Thị Thùy (VNU Journal of Foreign Studies; Vol 31 No 4, 2015)
Based on the theories of cross-cultural communication, this study aims at investigating the similarities and differences in expressing satisfaction towards different co-interactants in the Vietnamese and American languages and cultures. It focuses primarily on the popularity of strategies of expressing satisfaction employed. The author takes into consideration such informants’ social parameters as age, gender, marital status, living area, and knowledge of foreign language(s). Keywords: Cross-cultural communication, expressing satisfaction, directness and indirectness.